História de vida e comportamento social do rato-de-espinho semi-fossorial Clyomys laticeps (Thomas, 1909) (Rodentia: Echimyidae) - Ferrando, Claire Pauline Röpke (2022)
Life history and social behavior data are lacking for species with elusive habits, as burrowing rodents. Social and reproductive interactions among individuals can be understood through spatial patterns, which consist of the set of movements of the individuals in a population. These movements reflect individual strategies to maximize reproductive success in response to individual, populational and environmental conditions. Therefore, the spatial patterns of a population determine the genetic structure of poplations and social system of species. Therefore, based on captures, spatial organization and genetic data, we unravel life history traits, as well as social organization and mating system of the free-living burrowing echimyid rodent, Clyomys laticeps at Parque Estadual da Serra de Caldas Novas (GO, Brazil), situated in the Cerrado biome. The population studied presented constant low density throughout the study, breeding activity throughout the year and a lack of biased sex ratio and dimorphism in body mass. Clyomys laticeps adults frequently overlapped their home ranges with each other, but cooccurrence in time and space was rare and was limited to male-female pairs, a pattern that is most consistent with a solitary lifestyle in which each adult individual occupies a distinct burrow system. Neither sex nor season of the year affected spatial overlap in the population; this outcome is consistent with evidence suggesting that reproduction in this species occurs throughout the year. Moreover, individual males overlapped spatially with multiple females and vice versa, evidence suggesting a mating system in which both sexes mate with multiple partners. Indeed, through parentage data, it was possible to confirm6 that females and males frequently mate with more than on partner e share them with other individuals of the same sex. Moreover, spatial genetic structure and high genetic diversity in the studied C. laticeps population revealed that dispersal by both sexes promoted inbreeding avoidance. The low population density may favor the solitary behavior and frequent dispersal in C. laticeps, since the individual costs associated to territory occupancy (e.g. competition), burrowing (e.g. energy demand to dig) and dispersal (e.g. predation risk) may be minimum. Collectively, results obtained may contribute to understand the factors that promote convergence and divergence in social evolution between echimyid rodents as well as between burrowing rodents.